Epidemiology of Vitiligo in Puerto Rico: Descriptive Study from 2017-2022 - Rothenberg-Lausell, Camille; Pelegrina-Perez, Tatiana; Ruiz-Gil, Paula; Colón, Francisco (Puerto Rico Health Sciences Journal, 2024)
Objective: Vitiligo is a dermatological autoimmune condition characterized by areas of progressive skin depigmentation. Vitiligo lesions are cosmetically disfiguring and associated with significant psychological conditions such as depression and anxiety and comorbidities such as thyroid disease and diabetes. All races, ethnicities, ages, and regions of the world are impacted by vitiligo, with a global prevalence of about 0.5-2%. Currently, there is no published information available on the prevalence of vitiligo in Puerto Rico. Our study’s aim was to estimate the prevalence of vitiligo among patients attending the specialized clinic of dermatology at UPR School of Medicine in Puerto Rico and describe the distribution of cases by age and sex. Methods: We performed a descriptive study to evaluate the patients attending the University of Puerto Rico School of Medicine Clinics from January 2017 to May 2022. Using ICD-10 code L80 and medical records, we identified 581 patients with vitiligo and their respective demographic data distributed by sex and age. Results: Of the 581 vitiligo patients, 350 (60.2%) were women, and 231 (39.8%) were men. The median age in the vitiligo population was 33.5 years. Out of the studied sample, 30.2% were under the age of 18. Overall, there was an estimated prevalence of 5.2%. Conclusion: We report a vitiligo prevalence of 5.2% in a specialized clinic in Puerto Rico, suggesting further studies are necessary to discover possible underlying factors contributing to this increased prevalence.